The Philosophy of Simone de Beauvior. - Simons, Margaret A. (Indiana University Press, 2007)
Since her death in 1986 and the publication of her diaries in 1990, interest in the philosophy of Simone de Beauvoir has never been greater. Margaret A. Simons and an international group of philosophers present sixteen essays that reveal Beauvoir as one of the 20th century's most important and influential thinkers. As they set Beauvoir's work into dialogue with Husserl, Merleau-Ponty, Heidegger, Foucault, Levinas, and others, these essays consider such questions as Beauvoir's philosophical relationship with Sartre; her ethic of the erotic; her views on marriage, motherhood, and female friend.